Biochemical wastewater from landfill leachate pretreated by microalgae achieving algae's self-reliant cultivation in full wastewater-recycling chain with desirable lipid productivity. (November 2021) - Zhang, Lijie; Zhang, Libin; Wu, Daoji; Wang, Lin; Yang, Zhigang; Yan, Wenbao; Jin, Yan; Chen, Feiyong; Song, Yang; Cheng, Xiaoxiang
Graphical abstract: Highlights: Biochemical wastewater from landfill leachate was applied directly to algal cultivation. The excellent algal growth of 1.06 g/L was achieved from the 2nd cultivation. Phosphorus replenishment into the wastewater doubled the yield of algae lipid. Producing biodiesel through the full recycling chain could save 99% of the cost. Abstract: Heightened awareness of additional pretreatment for wastewater, has driven studies towards building a full wastewater-recycling chain wherein the wastewater pretreatment is performed by microalgae themselves. We applied biochemical wastewater from landfill leachate with added K2 HPO4 (BWLL + P) directly to microalgal cultivation. The results showed that the pretreatment provided by the 1st cultivation reduced suspended solids by nearly half, greatly boosting microalgal growth, which thus yielded 1.06 g/L of dry mass and 87.06 mg/L·d of biomass productivity. From the 2nd to the 4th cultivation, lipid accumulation in BWLL + P was 1.12–1.27 times and 1.95–2.36 times higher than in BG11 and BWLL, respectively, mainly attributed to the comfortable environment engendered by the microalgal pretreatment and the organic carbon in the wastewater. Strikingly, the biodiesel production fed with BWLL + P could save 99% of the cost compared with in BG11. In combination, our pioneering full wastewater-recycling chain achieved microalgae's self-reliant cultivation, with wastewater nourishment.